Pengembangan Karir dan Kompensasi terhadap Kepuasan Kerja Pegawai Badan Pemberdayaan Masyarakat Desa - Libriana Susanti (IPM2KPE, 2021)
This study aimed at career development and compensation for job satisfaction of employees of the Community Empowerment Agency. The research sample consisted of 45 employees of the Community Empowerment Agency. With the data collection method in the form of a census, followed by the F test and T-test. The analysis results can be interpreted that X_1 (career development) showed a coefficient value of (0.412). From the resulted of the hypothesis testing together, the career development variable and the compensation variable as a whole have a significant effect on the employee job satisfaction variable at the Lahat Village Community Empowerment Agency. Keywords: Job Satisfaction, Compensation, and Career Development